Fabricate 2014: Negotiating Design & Making - Gramazio, Fabio; Kohler, Matthias; Langenberg, Silke (2017)
Following the inaugural FABRICATE conference 2011 in London, the most important forum for international discussion on digital fabrication in architecture has resumed by Fabio Gramazio and Matthias Kohler at ETH Zurich. In contrast to the projects presented in 2011 at the Bartlett School of Architecture, which were balanced between practice and research, the questions about design and materialisation in architecture, construction, engineering, manufacturing, material and software design currently seem to be driven more by research institutions and young start-up entrepreneurs than by architectural practice. While digital fabrication technologies are becoming common practice in architecture for prototyping as well as in the realisation of buildings, contemporary research does not just investigate their further development, but presents ways to integrate them already in an early design phase to definitely overcome the still prevalent separation of design and making.